1998
DOI: 10.1021/la9712707
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Interfacial Properties of Demixed Fluids Using Density Gradient Theory

Abstract: This paper deals with theoretical investigation of interfacial properties between two coexisting liquid or fluid phases in thermodynamical equilibrium. The Cahn-Hilliard gradient theory was combined with an activity coefficient model (Koningsveld-Kleintjens model) or with an equation of state (Sanchez-Lacombe lattice fluid model). Using an activity coefficient model, only one variable (concentration) changed passing the interface. The interfacial tension between demixed liquids was calculated for two systems (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 36 publications
0
67
0
1
Order By: Relevance
“…By using a similar analysis, i.e., an expansion in the spatial variation of the particle densities, but in conjunction with the Peng-Robinson equation of state, Carey and co-workers (32) obtained good agreement with experiment for mixtures of complex molecules including alkanes and alkyl alcohols. Later work by Cornelisse et al (33) on hydrocarbon mixtures with carbon dioxide has confirmed the efficiency of this approach, at least where the temperature is not too low, and applications to other complex fluids continue to appear (34). Lee et al (35,36) have applied both a mean-field theory, similar to our GvdW treatment except for the lack of nonlocal entropy, and molecular dynamics (MD) simulation to the same type of LJ models of binary mixtures to obtain density profiles and surface tension.…”
Section: Introductionmentioning
confidence: 92%
“…By using a similar analysis, i.e., an expansion in the spatial variation of the particle densities, but in conjunction with the Peng-Robinson equation of state, Carey and co-workers (32) obtained good agreement with experiment for mixtures of complex molecules including alkanes and alkyl alcohols. Later work by Cornelisse et al (33) on hydrocarbon mixtures with carbon dioxide has confirmed the efficiency of this approach, at least where the temperature is not too low, and applications to other complex fluids continue to appear (34). Lee et al (35,36) have applied both a mean-field theory, similar to our GvdW treatment except for the lack of nonlocal entropy, and molecular dynamics (MD) simulation to the same type of LJ models of binary mixtures to obtain density profiles and surface tension.…”
Section: Introductionmentioning
confidence: 92%
“…First the interfacial properties will be considered at atmospheric pressure. Keeping the pressure constant, the density gradient theory will be blended with an activity coefficient model [28]. The Cahn-Hilliard theory [29] describes the thermodynamic properties of a system where an interface exists between two equilibrium phases.…”
Section: Density Gradient Theory (Dgt)mentioning
confidence: 99%
“…Additionally, the interfacial properties (interfacial tension and interfacial profiles) were studied theoretically using a special version [28] of the density gradient theory, introduced by Cahn and Hilliard [29]. The combination of the LCT or the LCT with the Wertheim lattice-perturbation theory allows the investigation of the influence of association forces on interfacial properties.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous investigations, the preferential adsorption in the vapor-liquid interface depends on the size and interactions of the molecules; therefore, the models combining density (or volume) with the surface tension are more successful than the models utilizing only surface tension. The gradient theory of fluid interfaces [3][4][5] is one of the prediction models combining density (or volume) with the surface tension. The gradient theory has two inputs containing the Helmholtz free energy density and the influence parameter for the homogeneous and the inhomogeneous fluids, respectively.…”
Section: Introductionmentioning
confidence: 99%